Urban Planning in the Global South - de Satgé, Richard. author. aut Link
XV, 255 p.
Keywords: ‘Refusing to be drawn in by the universalising claims of planning theory, de Satgé and Watson are as attentive to the micro-politics of everyday life as to the global dynamics shaping the broader territory, offering new insights into the concept of ‘conflicting rationalities’. This book offers a springboard in the vital development of southern planning theory and practice.’ – Colin Marx, University College London, UK ‘This path breaking book will profoundly shape social science and planning debates about how urban planning, development programmes and governmentality become enmeshed in everyday practices of survival in poor neighbourhoods in the global South.’ – Steven Robins, University of Stellenbosch, South Africa This book addresses the on-going crisis of informality in rapidly growing cities of the global South. de Satgé and Watson advance a Southern perspective on planning theory identifying how key precepts informing urban planning theory and practice must change fundamentally if social conditions are to improve in these settings. They argue that such changes will require an understanding of the ‘conflict of rationalities’ at the heart of the encounters between state planning norms and those struggling to survive in informal settlements. The complex nature of these contestations is explored through an in-depth case study of Langa, a township in Cape Town, South Africa. This reveals the many layers that frame the conflicts between the ambitions of state planners, shack-dwellers and township residents, and examines how these have shaped the changing dynamics of power and permeated all state–society engagements in the planning process. Richard de Satgé is Director of Research at Phuhlisani, a non-profit company. He has 40 years’ experience working in NGOs across southern Africa as an educator and researcher with a focus on land, livelihoods, poverty and informality. Vanessa Watson is Professor in Planning at the University of Cape Town, South Africa, and a university Fellow. She conducts research through the African Centre for Cities. Her research over the last 35 years has focused on urban planning in the global South.